The potential role of hydrogen towards a low-carbon residential heating in Italy - Sergio Tavella; Michel Noussan (Fondazione Eni Enrico Mattei (FEEM), 2021)
Buildings' heating represents an important share of the total energy consumption in Italy, and to reach the challenging decarbonization targets set by the EU by 2050, a combination of measures and technologies will be required. This working paper presents an analysis of different scenarios comparing the penetration of buildings' heating technologies for the residential sector in Italy. The objective of the research is to evaluate the potential contribution of different technologies, with a particular focus of the role that hydrogen may have to play, compared to other solutions, including heat pumps and renewable natural gas. The analysis compares the potential role of these technologies in reaching a decarbonized residential heating by 2050, by also discussing the main barriers and opportunities that lie ahead. The scenarios are defined starting from historical data of heating systems stock and sales, integrated with the know-how of experts of the sector to compare different pathways based on electrification or renewable gases. The results show that a combination of technologies will be in any case required in the heating sector, but also that other external factors will be of paramount importance, including the electricity decarbonization and energy efficiency measures on the building stock.
Keywords: Q4; Q42; Q55; 330; Heating; Residential Buildings; Hydrogen; Heat Pumps; Scenarios